REGULASI EMOSI IBU MENDAMPINGI ANAK DALAM BELAJAR DIMASA PANDEMI COVID-19 - MINARNI, MINARNI (DIALEKTIKA, 2021)
Learning is a process of activities carried out by humans in the process of developing knowledge, skills or attitudes in changing one's behavior so that in the learning process it is necessary to select, compile and deliver information that is in accordance with the environment. Currently the learning process has shifted from home to a school place due to the Covid-19 Pandemic. Students continue to learn by using media in the network called online learning or online learning through mobile phones, gadgets, computers and laptops. The use of this learning method, not a few parents, especially mothers, require long adaptations and even raise emotions in understanding and assisting children in the learning process. Emotion regulation is a process or a person's way of expressing his emotions which is influenced by his skills to reason, describe, and consider things. This study uses a qualitative method with a phenomenological approach consisting of four research subjects through purposive sampling. The results showed that mothers who accompanied their children to study during the COVID-19 pandemic brought up various emotions, including negative emotions such as stress, silence, shouting and anger. In addition, they also feel positive emotions such as patient, sincere, accepting, resigned, happy, more attached to children. The conclusion in this study is that every mother has different emotional regulation abilities, this is influenced by individual differences, cognitive, attachment, and religiosity by trying to be a mother who understands her child's shortcomings, makes mutually agreed learning methods, participates in the learning process children, doing relaxation, discussing so that learning is achieved wellKeywords: Mother’s Emotion Regulation, Child Support, Covid-19 Pandemic